Body and experiment – reflecting Kawabata Yasunari's counter-aesthetics. Issue 1 (2nd January 2018) - Hijiya-Kirschnereit, Irmela
Abstract: From his earliest works, Kawabata, known as an explicit aestheticist, deals in his works with flawed and disabled bodies in contrast to beautiful ones, evoking feelings of revulsion, awkwardness, disgust and premonitions of decay and death. The dynamism created out of these tensions and ruptures in the aestheticized world is scrutizined as hidden counter-aesthetics through questions such as: Which kinds of impairments are to be observed? Can they be classified according to grades? Are there gender specificities? How are these tensions and ruptures organized, and which categories (semantic, biological, political, moral) are concerned? Which narratorial and other functions are served through the counter-image of the flawed (impaired) body? And finally, how do the findings from these investigations into the flipside, the 'Other' of Kawabata's aesthetic universe, contribute to complementary or alternative ways of reading and understanding his literature? In a final section, Kawabata's treatment of female bodies as a site of experimenting with extreme situations of passivity and agency is highlighted, challenging more conventional readings of this and other works. The works discussed are from a deliberately broad chronological and generic range, including canonical and popular works. They range from the newspaper novels 'Utsukushii!' (1927) and 'Maihime' (1950/1), the novel 'Senbazuru' (1952) to the stories and palm-of-the-hand stories 'Ningen no ashioto' (1925), 'Izu no odoriko' (1926), 'Mekura to shōjo' (1928), 'Utsukushiki haka' (1929) 'Hokuro no tegami' (1940), 'Sasabune' (1950), and, in the final section, 'Kataude' (1963/4) and 'Nemureru bijo' (1960/1).